Low-cost projectile launcher experimental kit / Puteri Noor Safura Megat Mahmud … [et al.] - Megat Mahmud, Puteri Noor Safura; Mustafa, Mas Fiza; Che Balian, Siti Rudhziah; Johari, Noor ‘Aisyah (Division of Research and Industry Linkages, 2017)
Projectile motion is an example of motion with constant acceleration when air resistance is ignored. An object becomes a projectile at the very instant when it is released and is influenced only by gravity. The x- and y- components of a projectile's motion are independent, connected only by time of flight. Projectile motion is one of the crucial topics to be taught to students in Foundation Physics course. The students often find it difficult to understand the concept of projectile motion due to theoretical learning, in regards to 21st century learning model, preferably students like to hands-on practice to gain exprience so that they can understand better. To unravel this matter, the experimental kit is introduced to help increase enthusiasm and comprehensibility of scientific-technical topics A-low-cost projectile launcher experimental kit as a teaching aid was designed in helping the students to visualize and demonstrate the concept of projectile motion. The purpose of this experimental kit is to show the students the trajectory and horizontal distance of a certain object being thrown by a projectile launcher by varying the angles of projection and the initial velocities. This kit is built from a PVC tube, its base is from wood and spring as the launcher. Such simplicity in building this kit and importantly low-cost can be facilitated to any other education institution to build or develop their own kit. This modest design can be used indoors as well as outdoors.